2013
DOI: 10.1155/2013/284025
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of a Natural Anti-Inflammatory Agent, Astragaloside IV, on Ischemic Acute Kidney Injury in Rats

Abstract: This study investigated the anti-inflammatory effects of astragaloside IV(AS-IV) on ischemia/reperfusion (IR) induced acute kidney injury (AKI) in rats. Experimental model of ischemic AKI was induced in rats by bilateral renal artery clamp for 45 min followed by reperfusion of 12 h and 24 h, respectively. AS-IV was orally administered once a day to rats at 10 and 20 mg·kg−1·d−1 for 7 days prior to ischemia. AS-IV pretreatment significantly decreased serum urea, creatinine, and cystatin C levels at 12 h and 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Interestingly, Astragaloside IV, one of the most active compounds isolated from a Chinese medical herb [30], could decrease the expression of collagen and fibronectin in a dose- and time-dependent manner. Further, this drug displayed a strong anti-fibrosis effect in vivo , consistent with previous studies [10,11,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Astragaloside IV, one of the most active compounds isolated from a Chinese medical herb [30], could decrease the expression of collagen and fibronectin in a dose- and time-dependent manner. Further, this drug displayed a strong anti-fibrosis effect in vivo , consistent with previous studies [10,11,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In rat models of ischemia and reperfusion, AS-IV prevented ischemia-induced AKI through inhibiting nuclear factor-kappa B (NF-κB)-mediated expression of inflammatory genes and upregulating p53-upregulated modulator of apoptosis (PUMA) [14,15]. Studies also found that AS-IV protected against ischemia-induced AKI by inhibiting oxidative stress and apoptosis pathways [16].…”
Section: Introductionmentioning
confidence: 99%
“…Renal ischemia reperfusion injury (IRI) is well known as a main cause of AKI [2] that may occur because of an abrupt decrease of renal blood flow, low flow state, diverse surgical procedures, or during the organ transplantation [3]. IRI can be an early outcome of a transplanted organ that may lead to acute rejection of graft and has adverse effects on long term graft survival [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Renal IRI induces renal dysfunction characterized by increasing levels of creatinine (Cr) and blood urea nitrogen (BUN) [6]. The search for a treatment to recover IRI is ongoing, but unfortunately, innovative interventions beyond supportive therapy are not currently available for IRI [3,4].…”
Section: Introductionmentioning
confidence: 99%